Biochar and soil water table management effects on nitrogen availability - Haruna, Ahmed Osumanu; Maikol, Nathaniel; Maru, Ali (Universiti Putra Malaysia Press, 2020)
This book provides essential information on how organic amendments especially chicken litter biochar and soil water levels can be used to manage nitrogen in rice cultivation. It introduces the challenges and the need for managing urea on a tropical mineral acid soils for optimum rice productivity. It also provides information on issues related to ammonia volatilisation and rice productivity on tropical mineral acid soils. This book also discusses the important roles of soil water levels in addressing issues which are associated to ammonia volatilisation especially for low land rice production.